The model of the public-private partnerships in the context of the United Nations reform and the achievement of the objectives set by the 2030 agenda - Nino, Michele (CUADERNOS DE DERECHO TRANSNACIONAL, 2024)
This article examines the public-private partnership model within the framework of the reform of the United Nations system and the achievement of the objectives set by the 2030 Agenda. The first part of the article is dedicated to the identification of the characteristics of the PPP in the legal system and international relations, while the second part analyzes the model issue in the context of the United Nations and its specialized agencies. In the third part, some legal issues relating to both the international legal status of PPPs and the configuration of their responsibilities under international law are examined. Finally, the fourth part highlights how the PPP model could represent a key tool in the future within the framework of the reform of the United Nations and the achievement of the objectives set by the 2030 Agenda
Keywords: Public-private partnership; United Nations reform; United Nations specialized agencies; Agenda 2030; personality and responsibility of the PPPs